2011
DOI: 10.1158/1535-7163.mct-11-0046
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Monoclonal Antibody to Periostin Inhibits Ovarian Tumor Growth and Metastasis

Abstract: Periostin, an extracellular matrix protein, is reported to be overexpressed in a variety of human cancers and its functions seem to be linked to tumor metastasis. Our previous results show that engineered periostin overexpression promotes ovarian tumor growth and dissemination in vivo. In this study, we developed a neutralizing monoclonal antibody to periostin, named MZ-1, and investigated its effects on human ovarian tumor growth and metastasis. Our in vivo studies showed significant growth inhibition by MZ-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…28,36 We used an alternative strategy of in vivo antisense administration after establishment of severe proteinuria and found that inhibition of periostin could remarkably diminish the inflammation and reverse the increase in proteinuria. The ability of periostin to play distinctive roles in crucial events during development of renal disease by promoting tissue inflammatory response, accumulation of extracellular matrix and podocyte damage underline periostin targeting as a potential efficient future treatment against CKD.…”
Section: Discussionmentioning
confidence: 99%
“…28,36 We used an alternative strategy of in vivo antisense administration after establishment of severe proteinuria and found that inhibition of periostin could remarkably diminish the inflammation and reverse the increase in proteinuria. The ability of periostin to play distinctive roles in crucial events during development of renal disease by promoting tissue inflammatory response, accumulation of extracellular matrix and podocyte damage underline periostin targeting as a potential efficient future treatment against CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of POSTN has been observed in various tumor types, including breast [44,48,[56][57][58], NSCLC [27,49,[59][60][61][62], colorectal [19,29,63], stomach cancers [64][65][66][67][68], pancreatic [32,69], prostate [70][71][72][73][74][75], ovarian cancer [76][77][78][79], and glioblastomas [80][81][82] (Table 1).…”
Section: Periostin Expression In Different Types Of Tumorsmentioning
confidence: 99%
“…In vivo Antibody directed against POSTN (MZ-1) inhibits the development of primary tumors derived from the periostin-expressing ovarian cancer cell line A2780 [77] Ovarian cancer IHC Expression of POSTN in cancer-associated stromal fibroblasts, but not in cancer cells. The 5-year survival rate was better in patients with negative POSTN expression than in those with positive POSTN expression.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…28 Zhu 2011: Neutralizing monoclonal antibody to periostin inhibited anchorage-independent growth of the periostin-expressing ovarian cancer cell line A2780. 38 Zhu 2011: Neutralizing monoclonal antibody to periostin inhibited periostin-induced cancer cell migration and invasion. 38 Jackson-Boeters 2009: Periostin expression coincides with 〈-SMA expression within the granulation tissue of excisional wounds of mice.…”
Section: /2mentioning
confidence: 99%
“…38 Zhu 2011: Neutralizing monoclonal antibody to periostin inhibited periostin-induced cancer cell migration and invasion. 38 Jackson-Boeters 2009: Periostin expression coincides with 〈-SMA expression within the granulation tissue of excisional wounds of mice. 10 Liu 2010: Inhibition of periostin expression via RNA interference suppressed proliferation of a human osteosarcoma cell line (U2OS).…”
Section: /2mentioning
confidence: 99%